Iron Ores - Shatokha, Volodymyr (IntechOpen, 2021)
This book provides the multidisciplinary reader with a comprehensive state-of-the-art overview of research, technologies, and innovations related to iron ores. The content embraces industrial sectors and technologies dealing with mining and processing of iron ores; therefore, it covers a wide range of research fields including geoscience, deposit exploitation, resource development, comminution, beneficiation, sintering and reduction, etc. Innovations and industrial synergies across the entire production chain are broadly addressed. This book also represents advanced research methods with a focus on the genesis, mineralogy, characterization, mechanical and physicochemical properties, and environmental aspects. Interdisciplinary topics reflect cutting-edge research often reaching beyond the conventional boundaries and traditional themes.